(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article, the role of parents in the process of integration of hearing impaired children into society, their correction, compensation and rehabilitation and the analysis of the world experience of bringing parents into this process were studied.